2007
DOI: 10.1093/cercor/bhm239
|View full text |Cite
|
Sign up to set email alerts
|

Depression of Human Corticospinal Excitability Induced by Magnetic Theta-burst Stimulation: Evidence of Rapid Polarity-Reversing Metaplasticity

Abstract: Metaplasticity refers to the activity-dependent modification of the ability of synapses to undergo subsequent potentiation or depression, and is thought to maintain homeostasis of cortical excitability. Continuous magnetic theta-burst stimulation (cTBS; 50 Hz-bursts of 3 subthreshold magnetic stimuli repeated at 5 Hz) is a novel repetitive magnetic stimulation protocol used to model changes of synaptic efficacy in human motor cortex. Here we examined the influence of prior activity on the effects induced by cT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
267
8
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(294 citation statements)
references
References 42 publications
18
267
8
1
Order By: Relevance
“…That corticospinal excitability was reduced in VolϩrTMS but not in Vol is evidence that such an interaction occurred. Such an interaction was also demonstrated in a different experimental context in which theta-burst stimulation given after a voluntary contraction inhibited MEPs (21). Still, the precise mechanism of how rTMS interfered with motor performance is unclear.…”
Section: Role Of Primary Motor Cortex In Maximal Voluntary Forcementioning
confidence: 90%
See 1 more Smart Citation
“…That corticospinal excitability was reduced in VolϩrTMS but not in Vol is evidence that such an interaction occurred. Such an interaction was also demonstrated in a different experimental context in which theta-burst stimulation given after a voluntary contraction inhibited MEPs (21). Still, the precise mechanism of how rTMS interfered with motor performance is unclear.…”
Section: Role Of Primary Motor Cortex In Maximal Voluntary Forcementioning
confidence: 90%
“…Highfrequency (Ͼ1 Hz) rTMS tends to increase corticospinal excitability, and low-frequency rTMS (Յ1 Hz) administered below, at, and above resting motor threshold (rMT) tends to decrease corticospinal excitability that can last for up to an hour after the stimulation is stopped (26,45). Even highfrequency magnetic brain stimulation in the form of continuous magnetic theta-burst stimulation, when administered after voluntary contractions, can depress corticospinal excitability (21). Several studies demonstrated that the reduction in corticospinal excitability was not accompanied by a reduction in motor output (11,40,43,58).…”
mentioning
confidence: 99%
“…We then explored the effects of the cTBS protocol, which also induces plasticity effects (LTP or LTD) in healthy individuals (Gentner et al, 2008;Iezzi et al, 2008;Huang et al, 2011). Repeated-measures ANOVA showed a significant effect of GROUP (F ϭ 3.83, p Ͻ 0.05) and a significant TIME per GROUP interaction (F ϭ 4.15; p Ͻ 0.05).…”
Section: Ltp Induction In the Motor Cortex Of Rr-ms And Of Pp-msmentioning
confidence: 99%
“…One recently developed variant of repetitive transcranial magnetic stimulation (TMS), continuous theta burst stimulation (cTBS;Huang et al 2005), has shown promise because of its rapid application (Ͻ1 min), its ability to produce behavioral effects for up to 1 h after stimulation, and its connection to known neuronal mechanisms, such as long-term potentiation and depression (LTD). Indeed, research has shown that cTBS reduces motor cortical excitability in a manner consistent with LTD effects (Allen et al 2007;Di Lazzaro et al 2005Gentner et al 2008;Huang et al 2005Huang et al , 2007.…”
mentioning
confidence: 91%
“…One recently developed variant of repetitive transcranial magnetic stimulation (TMS), continuous theta burst stimulation (cTBS;Huang et al 2005), has shown promise because of its rapid application (Ͻ1 min), its ability to produce behavioral effects for up to 1 h after stimulation, and its connection to known neuronal mechanisms, such as long-term potentiation and depression (LTD). Indeed, research has shown that cTBS reduces motor cortical excitability in a manner consistent with LTD effects (Allen et al 2007;Di Lazzaro et al 2005Gentner et al 2008;Huang et al 2005Huang et al , 2007.When applied to the occipital cortex, cTBS has been found to increase phosphene thresholds (PTs), such that higher stimulation intensity is needed to produce conscious visual experience (Franca et al 2006). One possibility is that such an increase in PTs is, at least in part, due to decreased connectivity between areas in the early visual cortex, which would make the Here we tested for this possibility by investigating the resting state connectivity between retinotopically defined regions in the early visual cortex after occipital application of cTBS.…”
mentioning
confidence: 96%